1984
DOI: 10.1007/bf01868439
|View full text |Cite
|
Sign up to set email alerts
|

Effects of antidiuretic hormone on cellular conductive pathways in mouse medullary thick ascending limbs of Henle: I. ADH increases transcellular conductance pathways

Abstract: This paper reports experiments designed to assess the relations between net salt absorption and transcellular routes for ion conductance in single mouse medullary thick ascending limbs of Henle microperfused in vitro. The experimental data indicate that ADH significantly increased the transepithelial electrical conductance, and that this conductance increase could be rationalized in terms of transcellular conductance changes. A minimal estimate (Gminc) of the transcellular conductance, estimated from Ba++ bloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
106
0

Year Published

1986
1986
2000
2000

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(127 citation statements)
references
References 38 publications
21
106
0
Order By: Relevance
“…In these studies chloride transport was reduced and acidosis did not significantly affect chloride transport. Although there appeared to be greater variation in the effect of acidosis on chloride transport in the cTALH in the absence of luminal K, the simplest and most direct interpretation of these results is that chloride reabsorption depends on luminal potassium (consistent with the observations of other investigators 116, [25][26][27]) and that the effect ofan even greater degree ofperitubular acidosis cannot be demonstrated under these conditions. The degree of inhibition of chloride transport in the absence of luminal K is greater in the present study than in previous reports (28).…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…In these studies chloride transport was reduced and acidosis did not significantly affect chloride transport. Although there appeared to be greater variation in the effect of acidosis on chloride transport in the cTALH in the absence of luminal K, the simplest and most direct interpretation of these results is that chloride reabsorption depends on luminal potassium (consistent with the observations of other investigators 116, [25][26][27]) and that the effect ofan even greater degree ofperitubular acidosis cannot be demonstrated under these conditions. The degree of inhibition of chloride transport in the absence of luminal K is greater in the present study than in previous reports (28).…”
Section: Resultssupporting
confidence: 80%
“…Similar effects of acidosis have been reported for the proximal convoluted tubule (24) and the medullary thick ascending limb of Henle (mTALH) (25). Recent work in the mTALH suggests that sodium chloride entry depends on potassium conductance and luminal potassium cotransport (26,27). To examine whether potassium-coupled sodium chloride entry was critical for the inhibition of chloride transport due to acidosis, a separate set of experiments was performed in which luminal potassium was removed.…”
Section: Resultsmentioning
confidence: 99%
“…Mops, 3-(N-morpholino)-propanesulfonic acid; PMSF, phenylmethylsulfonyl fluoride; TAL, thick ascending limb of Henle's loop; TFP, trifluoperazine luminal membrane together with the Na+,K+ pump and a net Cl-conductance in the basolateral membrane [1,2]. The K+ channel is stimulated by Ca*+ in physiological concentrations [3,4] and may thus be involved in regulation of transepithelial NaCl transport.…”
Section: Abbreviationsmentioning
confidence: 99%
“…TAL is involved in two main reabsorptive functions which are sodium chloride reabsorption, contributing to the generation of the corticopapillary gradient, and the reabsorption of the bulk of the filtered calcium and magnesium. Since chloride transport has been shown to be closely correlated to sodium transport as well as to the passive reabsorption of the divalent cations (8,9), Jcl, determined on microperfused tubules, was used as the representative parameter of the TAL function. The fact that, in the present study, the inhibitory effect of PAF on Jcl was found to be similar in the cortical TAL (cTAL) and in the mTAL allowed us to investigate the mechanism of action involved in this effect on either segment.…”
Section: Introductionmentioning
confidence: 99%